'Mart of the World': an architectural and geographical history of the London Stock Exchange. Issue 5 (3rd July 2016) - Thomas, Amy
Abstract : A stock exchange is a spatial contradiction. Conceived as a marketplace for the trade in securities and other financial instruments, it is intended to provide a regulated forum as a fair and free market for its members: an open economic environment made possible by institutional confinement. Once the largest and most influential in the world, the London Stock Exchange (LSE) embodied this contradiction. Established in the heart of the imperial metropolis, the LSE emerged at the core of a global financial network that sustained Britain's territorial and 'informal' Empire. Concurrently, its self-regulated standing within the City of London and reliance on an esoteric world of gentlemanly connections positioned it as an establishment shaped and assisted by its locality. Established to finance overseas trade in the seventeenth century, the London stock market materialised as the informal appendage of commodity markets in the alleyways surrounding the Royal Exchange. The next three hundred years saw the consolidation and growth of the LSE from classicising institutional grandeur, to concrete monolith in the 1970s and most recently, to the corporate serenity of Paternoster Square. In mapping the movement of global markets alongside the shifting terrain of the LSE buildings, this paper addresses the manner in which the latter reflects the geographical scope of Britain's capital accumulation throughout the last three centuries. The LSE is looked at in the context of the rise and fall of the British Empire and in its more recent role as channel for international (and offshore) capital, in order to assess whether its architectural choices might reflect shifting attitudes towards economic expansion. At present there are no dedicated architectural accounts of the LSE at any point of its existence. This paper intends to traverse the gap between economic geography and architectural history by means of a methodology of spatial scales, moving from the cartographic to the bodily. In producing a dialogue between macroscopic and microscopic analysis, this enquiry intends to expose more tangible interpretations of an immaterial system that increasingly distorts our material reality.